Isu-isu Global dalam Khazanah Tafsir Nusantara - Fikriyati, Ulya (SUHUF, 2013)
In this study, the four global issues that questioned the perspective of Islam on will be discussed through the portrait of the commentary of the Quran of the Indonesian Archipelago offered by M. an-Nawawi al-Jawi and that of M. Quraish Shihab. They are the two exegetes of the Qur’an of the Indonesian origin who live in different places and at different times, with different backgrounds and both wrote the commentary of the Qur’an in different language. This writing tries to find both similarity and difference from those two commentaries of the Qur’an which at least have given a description about the heterogeneous commentary of the Qur’an of the Indonesian Archipelago. Those four issues are the issue of religious tolerance, that of peace, that of anti-terrorism, that of human dignity and that of human equality.Keywords: Nawawi, Quraish Shihab, religious tolerance, peace, anti terrorism, human equality.